Jewish autonomy in a slave society : Suriname in the Atlantic world, 1651-1825 - Ben-Ur, Aviva (Early modern Americas., 2020)
"This book looks at the Jewish population of Surname from 1651 to 1825. In Surname, Jews had more autonomy than anywhere else in the world. The Jewish settlement there was one of the earliest Jewish settlements in the Western Hemisphere"--